The Precious Girth of Russia - Kudryavtsev, Alexander (project baikal, 2019)
The significance of the small historical towns is still rather important in the system of settlement of Russia, its culture and history as well, its population is yet great. But the process of commercial urbanization stopped their development. Beginning from the 1990s, the RAACS has been investigating the issue, considering participation of all layers of citizens, improving the management and the juridical basis of these activities to be the key directions of their renaissance. Different examples of practices dealing with this kind of settlements are given.
Keywords: small historical town; cultural heritage; management; settlement; participation